Risk factors for Clostridium difficile infection in HIV-infected patients. (14th December 2016) - Imlay, Hannah; Kaul, Daniel; Rao, Krishna
Background: Clostridium difficile infection is a healthcare-associated infection resulting in significant morbidity. Although immunosuppression is associated with Clostridium difficile infection acquisition and adverse outcomes, the epidemiology of Clostridium difficile infection in HIV-infected patients has been little studied in the era of antiretroviral therapy. This study identifies the risk factors for acquisition of Clostridium difficile infection in HIV-infected patients. Methods: A retrospective, propensity score–matched case–control study design was employed, with patients selected from our institution's outpatient HIV clinic. Clostridium difficile infection cases were defined as having positive stool testing plus an appropriate clinical presentation. The propensity score was generated via multiple logistic regression from year of HIV diagnosis, age at first contact, duration of follow-up, gender, and initial CD4 count. Results: The 46 cases included were matched to a total of 180 controls. Prior antibiotic treatment was a significant predictor of Clostridium difficile infection (odds ratio: 13, 95% confidence interval: 3.49–48.8, p  < .001) as was number of hospital admissions in the preceding year (odds ratio: 4.02, confidence interval: 1.81–8.94, p  < .001). Having both proton pump inhibitor use and CD4 count <200 cells/µL significantly increased odds of Clostridium difficile infection in the multivariable model (odds ratio: 15.17, confidence interval: 1.31–175.9, p  = .021). Conclusion: As in the general population, frequent hospitalizations and exposure to antimicrobials are independent predictors of Clostridium difficile infection acquisition in patients with HIV. Additionally, low CD4 count and proton pump inhibitor use are new potentially modifiable variables that can be targeted for prevention of Clostridium difficile infection in future interventional studies.